SIMULATION OF RESONANT REACTIONS IN TTIK APPROACH BY C++ CODE (International Journal of Mathematics and Physics, 2025)
We studied the interaction of ¹⁵N with hydrogen at low energies using the Thick Target Inverse Kinematics (TTIK) method combined with the Time of Flight (ToF) technique. This combination enables a clear identification of different light recoil particles without compromising energy resolution in the extended gas target. The use of a gas target ensures minimal background and allows precise measurement of energy loss and reaction kinematics across a broad excitation function. At the same time, the ToF technique provides particle separation without degrading energy resolution. In this paper, we presented the results of theoretical calculations of energy losses in the gas target, implemented using a custom C++ code. The obtained results show reasonable agreement with experimental data. The simulations agree well with the experimental results for α-particles and ¹²C nuclei, confirming the accuracy of the theoretical predictions for these reaction products. However, further improvements or theoretical refinements are required due to the insufficient fit observed in the proton-related calculations.Keywords: TTIK, inverse kinematics, time of flight, resonant reaction, C++ simulation.